Penerapan Metode Rapid Application Development (RAD) dalam Pelatihan Pembuatan Aplikasi Sederhana - Amanda, Aliza Fatha; Afrizal, Muhammad Fahri; Sugiarti, Yuni (Journal Of Computer Science Contributions (JUCOSCO), 2024)
Efficient and effective software development is becoming increasingly important in today's digital age. The purpose of this paper is to assess the success of RAD implementation by taking into account the advantages and disadvantages, challenges faced, and how to make RAD implementation run effectively. The method used in this writing is a literature study. From the results obtained, it can be concluded that in the implementation of the RAD method, it is necessary to pay attention to what projects are being run, whether human resources are sufficient, and what applications are developed. This needs to be done because RAD is not a suitable method for all types of applications, especially new applications. The use of the right tools is highly recommended to support rapid development. The success of RAD is highly dependent on the project context and the capabilities of the development team, and further research is needed to evaluate the effectiveness of RAD in different types of software projects.